The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1414-431x20165674
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy with trastuzumab in HER2-positive breast cancer: pathologic complete response rate, predictive and prognostic factors

Abstract: The purpose of this study was to retrospectively review the pathologic complete response (pCR) rate from patients (n=86) with stage II and III HER2-positive breast cancer treated with neoadjuvant chemotherapy at our institution from 2008 to 2013 and to determine possible predictive and prognostic factors. Immunohistochemistry for hormone receptors and Ki-67 was carried out. Clinical and pathological features were analyzed as predictive factors of response to therapy. For survival analysis, we used Kaplan-Meier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…While it is difficult to compare pCR rates with historical data due to different grouping strategies, in this study, the pCR rate in trastuzumab-treated patients was not affected by region, or by age, in line with some previous observations [9]. A lower pCR rate was observed among patients with later stage disease, per other reports [10, 11]. Nevertheless, pCR rates were similar between trastuzumab and CT-P6 groups, across subgroups.…”
Section: Discussionsupporting
confidence: 88%
“…While it is difficult to compare pCR rates with historical data due to different grouping strategies, in this study, the pCR rate in trastuzumab-treated patients was not affected by region, or by age, in line with some previous observations [9]. A lower pCR rate was observed among patients with later stage disease, per other reports [10, 11]. Nevertheless, pCR rates were similar between trastuzumab and CT-P6 groups, across subgroups.…”
Section: Discussionsupporting
confidence: 88%
“…NAC has been shown to modify the extent of pathological disease found in axillary lymph nodes in ~20–40% of patients ( 2 , 3 ). The trastuzumab-based NAC regimen has shown a greater pCR rate ( 16 , 17 ). A potential down-staging represents a challenge to the indications for PMRT.…”
Section: Discussionmentioning
confidence: 99%
“…The newer NAC regimens have increased the percentage of pCR ( 16 , 17 , 22 ). One study reported that 46.8% of HER2-positive breast cancer patients subjected to neoadjuvant chemotherapy with trastuzumab achieved a pCR ( 16 ). However, few published studies have demonstrated how pCR status affects locoregional treatment choices.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic antibody trastuzumab (Herceptin®) was used as a model substance for studying the molecular integrity during the application of different kinds of thermal stresses, for example, during thermal unfolding and during liquid storage at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%